An analysis of experimental activities in Chemistry based on the Dimensions of Scientific Learning - Lima , Keila Padilha de Oliveira Camargo de (2024)
This research presents the results of an investigation that aimed to identify and analyze the Dimensions of Scientific Learning mobilized by students when answering open questions from pre- and post-experiment activities in remote Chemistry classes. To this end, student responses were analyzed in activities that addressed topics such as bean plantation and the Dead Sea, seeking to identify these dimensions (NRC, 2012; NGSS, 2013). Through the analyses, based on the assumptions of content analysis, six Scientific Practices related to doing Science were identified, four Transversal Concepts, which cross disciplinary boundaries, ranging from the identification of patterns to the recognition of the causes and effects of the phenomena under study and two groups of Disciplinary Central Ideas, related to specific scientific concepts. By engaging in the proposed activities, students were able to get involved in different Dimensions, providing for them to build a broader understanding of the ideas of Science.